PENGARUH PER, DER, DAN DPR TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Devianasari, Ni Luh; Suryantini, Ni Putu Santi (E-Jurnal Manajemen; Vol 4 No 11 (2015), 2015)
This research was conducted in Manufacturing companies in Indonesia Stock Exchange 2009-2013 period. By using purposive sampling method obtained a sample of 10 companies from the population of 176 companies. Data collected by using observation method nonparticipant through the annual financial statements that are accessed through the official website of the Indonesian Stock Exchange (BEI) and the Indonesian Capital Market Directory (ICMD). The data analysis technique used is multiple linear regression. The results showed that the regression model used has fulfilled classical assumption test. From the research results can be known simultaneously the price earnings ratio, debt to equity ratio, dividend payout ratio simultaneously significant positive effect on the value of the company, while partial price earnings ratio significant negative effect on the value of the company. Debt to equity ratio significantly positive effect on firm value. Dividend payout ratio is not significant positive effect on firm value.
Keywords: price earning ratio; debt to equity ratio; dividen payout ratio; nilai perusahaan